Food consumption of users of the Primary Health Care network, with chronic non-communicable diseases in Ponta Grossa, Paraná: cross-sectional study, 2023 - Batistel Szczerepa, Sunali (2024)
Objective: to evaluate the food consumption of users of Primary Health Care (PHC) with chronic non-communicable diseases (NCDs). Methods: Cross-sectional study, developed from the Capacita Chronic Diseases Project, in 8 basic health units with 280 users, over 18 years old, with one or more of the NCDs selected for the study (obesity, diabetes and/or hypertension). Sociodemographic and economic data, past health history and dietary frequency were collected using two forms. An association was found between food consumption and socioeconomic, demographic and health condition variables. Results: The majority of users were women (74.3%), white users were more frequent (75.7%) and the average age was 59.8 years. The majority were married (53.9%) and retired (38.6%). The most common level of education was primary education (61.8%) and income was 1-3 minimum wages (58.9%). The most consumed foods (in average score) were: fresh or minimally processed foods (2.9±1.1), followed by culinary ingredients (2.8±1.7), processed foods (2.2± 0.9) and, finally, ultra processed foods (1.8±0.9). The socioeconomic variable education (n=10), the demographic housing situation (n=15) and the health condition diabetes (n=10) were those that reached the highest quantity of foods/food groups with statistically significant differences. Conclusion: Although fresh or minimally processed foods are the basis of users' diet, the intake of ultra-processed foods is still frequent, which is mainly influenced by education, housing situation and the presence of diabetes.